Recruiting Domestically Violent Fathers and Families for Research: What Does It Take?. Issue 9 (21st October 2021) - Dyson, Amanda; David, Randal; Scott, Katreena
ABSTRACT: Empirical literature on strategies to effectively recruit participants for research is sparse, especially within the domestic violence domain. Evaluating recruitment methodology alongside researcher effort, time, and costs provides realistic guidelines for research planning. This study examined recruitment of fathers with and without a history of domestic violence perpetration into longitudinal research. Data were collected on 196 fathers we attempted to recruit for Time 1 assessment and 151 fathers we attempted to retain for Time 2 assessment over an eight-month timeframe. Results indicated that domestically violent fathers required similar efforts to recruit initially but required more effort for follow-up and that recruitment for father-child and mother assessments with this group was particularly challenging. Tests of two specific recruitment strategies demonstrate advantages of in-person and immediate scheduling of research appointments. Descriptive information is provided on the time and resources required for recruiting high-risk fathers into research and recommendations for conducting future research with this population are provided.